2020
DOI: 10.1007/s00464-020-07565-w
|View full text |Cite
|
Sign up to set email alerts
|

SAGES and EAES recommendations for minimally invasive surgery during COVID-19 pandemic

Abstract: The unprecedented pandemic of COVID-19 has impacted many lives and affects the whole healthcare systems globally. In addition to the considerable workload challenges, surgeons are faced with a number of uncertainties regarding their own safety, practice, and overall patient care. This guide has been drafted at short notice to advise on specific issues related to surgical service provision and the safety of minimally invasive surgery during the COVID-19 pandemic. Although laparoscopy can theoretically lead to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
268
0
13

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 198 publications
(282 citation statements)
references
References 22 publications
1
268
0
13
Order By: Relevance
“…At the same time, it is of importance to maintain equipoise for non-Covid-19 patients despite decreased resources. Adaptations of surgical guidelines are required, as recommended by various scientific societies [ 6 , 17 , 18 ]. Thus, the “ primum non nocere ” principle has to be applied not only for Covid-19, but all patients.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, it is of importance to maintain equipoise for non-Covid-19 patients despite decreased resources. Adaptations of surgical guidelines are required, as recommended by various scientific societies [ 6 , 17 , 18 ]. Thus, the “ primum non nocere ” principle has to be applied not only for Covid-19, but all patients.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, studies have shown that similar virus can be retrieved in surgical smoke (HBV, HIV, and HPV) [11], so great care should be taken to reduce aerosolisation and direct contamination. The risk of contagion is unlikely when general prevention strategies have been applied as recommended by the other societies (SAGES-EAES [12], ACS):…”
Section: Is Minimal Invasive Surgery Safe In the Emergency Setting?mentioning
confidence: 99%
“…There is no evidence for contraindication of the laparoscopic approach. In fact, the laparoscopic approach seems to allow better control of surgical smoke/plume than laparotomy [12]. 2.…”
Section: Is Minimal Invasive Surgery Safe In the Emergency Setting?mentioning
confidence: 99%
See 2 more Smart Citations